2010
DOI: 10.1309/ajcpldt9ovx1tdgt
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Plasma With Whole Blood Prothrombin Time and Fibrinogen on the Same Instrument

Abstract: We compared plasma with whole blood (WB) international normalized ratio (INR) and fibrinogen using the same instrument and reagents. WBINRs were 50% higher than plasma INRs. After increasing the WB sample volume 40% and adjusting the International Sensitivity Index, WBINRs were similar to plasma INRs [adjusted WBINR = 0.99(plasma INR) - 0.02; r(2) = 0.98; n = 155], but the average difference in WB vs plasma INR was 4-fold higher than duplicate plasma INRs. Variation in hematocrit was a major determinant of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…One problem with pointof-care assays, whether they use standard or viscoelastic methodology, is variation due to the effect of hematocrit on the effective plasma sample volume in the assay. In one study, whole-blood INRs were similar to plasma INRs, but the whole-blood assays showed more variability [14]. Variation in hematocrit was the major determinant of the accuracy of the whole-blood INR, with increased error at higher INRs.…”
Section: Standard Assaysmentioning
confidence: 96%
See 1 more Smart Citation
“…One problem with pointof-care assays, whether they use standard or viscoelastic methodology, is variation due to the effect of hematocrit on the effective plasma sample volume in the assay. In one study, whole-blood INRs were similar to plasma INRs, but the whole-blood assays showed more variability [14]. Variation in hematocrit was the major determinant of the accuracy of the whole-blood INR, with increased error at higher INRs.…”
Section: Standard Assaysmentioning
confidence: 96%
“…Due to the slow turnaround time for fibrinogen assays in many central clinical laboratories [6], rapid whole-blood estimates of fibrinogen can be made using viscoelastic assays, but wholeblood measurements of fibrinogen are affected by the hemocrit in the sample being tested. As discussed above, hematocrit must be taken into account when interpreting whole-blood fibrinogen results [14].…”
Section: Viscoelastic Global Hemostasis Ass Aysmentioning
confidence: 99%
“…Accuracy is limited by variations in haematocrit [20], and is worse for high INRs and low fibrinogens. Within the range of INR (1.5-2.5) where decisions are usually taken to initiate treatment, it has acceptable accuracy and compares well with conventional coagulation tests [21]. Before introducing any POC technology it is essential to evaluate the performance in the specific context of their potential use against central laboratory tests [22].…”
Section: Simple Poc Tests Of Coagulationmentioning
confidence: 99%
“…The turnaround time for selected tests can be substantially shortened by attention to the processing details and policies [36]. Although point-of-care, whole-blood coagulation tests offer promise, results for the prothrombin time/International Normalized Ratio and fibrinogen may be dependent on the hematocrit and difficult to standardize for samples with abnormal values [38]. Key factors that need to be considered in the execution of traditional laboratory tests with rapid turnaround time are listed in Table 2.…”
Section: Question 5 Usefulness Of Laboratory Tests: What Do Coagulatmentioning
confidence: 99%